ANALISIS PENERAPAN DISKRESI DALAM PENGISIAN JABATAN WAKIL GUBERNUR PROVINSI KEPULAUAN RIAU DIHUBUNGKAN DENGAN UU PILKADA JO UU ADMINISTRASI PEMERINTAHAN / ANALYSIS OF THE APPLICATION OF DISCRETION IN FILLING IN THE POSITION DEPUTY GOVERNOR OF RIAU ISLANDS PROVINCE IS LINKED TO THE REGIONAL ELECTION ACT AND GOVERNMENT ADMINISTRATION ACT - PERY REHENDRA SUCIPTA (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2018)
Provinsi Kepulauan Riau menghadapi persoalan ketika terjadinya kekosongan jabatan wakil gubernur dalam penyelenggaraan pemerintahan. Hal ini berdampak pada tidak berjalannya secara efektif roda pemerintahan dalam rangka demokratisasi dan percepatan pembangunan di daerah. Sementara regulasi yang secara khusus (peraturan pemerintah) yang mengatur tentang tata cara pengusulan dan pengangkatan calon Wakil Gubernur belum diterbitkan, sebagaimana amanat Pasal 176 Ayat (5) UU Pilkada. Dengan pendekatan Yuridis Normatif dalam penelitian ini, penulis mengkaji tentang bagaimanakah keberlakuan Pasal 176 UU Pilkada sebelum diterbitkannya Peraturan Pemerintah dan apakah mekanisme Diskresi yang dikenal dalam Hukum Administrasi Negara dapat di terapkan dalam pengisian jabatan Wakil Gubernur Provinsi Kepulauan Riau. Hasil pada penelitian ini adalah: Pertama, Pasal 176 UU Pilkada tidak dapat diberlakukan karena belum diterbitkannya peraturan pemerintah sebagaimana perintah dari Pasal 176 ayat (5) UU Pilkada. Kedua, mekanisme Diskresi seharusnya dapat di terapkan dalam pengisian jabatan Wakil Gubernur Provinsi Kepulauan Riau. Pertimbangan karena sejalan dengan tujuan penggunaan diskresi diantaranya untuk melancarkan penyelenggaraan pemerintahan, mengisi kekosongan hukum dan memberikan kepastian hukum.The province of Riau Islands face the problem when the occurrence of the vacancy the post of deputy governor in the administration of government. This has an impact on not progressed effectively the wheels of government in order to democratize and acceleration of development in the area. While the regulation specifically (government regulation) which regulates the procedures of proposal and appointment of candidates for the Deputy Governor has not been published, as mandated by Article 176 Paragraph (5) of the Election ACT. With Normative Juridical approach in this study, the authors examine on how the applicability of Article 176 of the Law Elections before the issuance of Government Regulation and whether the mechanism of Discretion that is known in Administrative Law can apply in filling the post of Deputy Governor of Riau Islands Province.The results in this study are: First, Article 176 of the Law on Elections cannot be applied because it has not been the issuance of government regulation as the command of Article 176 paragraph (5) of the Election ACT. Second, the mechanism of Discretion should be applied in the filling of the post of Deputy Governor of Riau Islands Province. Consideration because it is in line with the purpose of the use of discretion among them to launch the organization of the government, filling the void of law and provide legal certainty.